ZAŁOŻENIA FENOMENOLOGICZNE I KONSTRUKTYWISTYCZNE JAKO PODSTAWY TEORII KOMUNIKACJI W SOCJOLOGII RELIGII - Zduniak, Agnieszka (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The paper presents main themes of sociological and philosophical thought which contributed to establishment of communicative orientation in sociology of religion. According to numerous sociologists, it constitutes a new perspective providing an explanation and description of contemporary forms in which religion is manifested, and also a broad spectrum of phenomena in the field of spirituality. Observation of forms of communication may help to notice changes in the sphere of religion as well as their connection with particular cultural changes. The author presents sociological and philosophical conceptions in which the subject of sense and its communication is taken up; from interpretive sociology by M. Weber, phenomenological sociology, social constructivism, conception of communication by N. Luhmann through contemporary sociological conceptions that may be included in a current of communicative constructivism. The author reflects on possibilities of applying the communicative conception in the field of sociology of religion and sociology of spirituality.